Critical government strategies for enhancing building information modeling implementation in indonesia - Rani, Hafnidar A.; Al-Mohammad, Mohammad S.; Rajabi, Mohammad Sadra; Abdul Rahimi, Abdul Rahman (MDPI, 2023)
Building information modeling (BIM) enables substantial improvement in the architect, engineering, and construction (AEC) industry. To enhance BIM implementation, policymakers should develop appropriate strategies addressing local AEC industry needs. However, prior works that have explored government strategies to enhance BIM implementation in Indonesia are scarce. Therefore, this study aimed to investigate the critical government strategies to enhance BIM implementation in Indonesia. A systematic literature review and semi-structured interviews with AEC professionals yielded 12 potential government strategies. The data were analyzed using mean score ranking, normalization, overlap, agreement, and correlation analyses. The findings illustrate that six strategies are critical for enhancing BIM implementation in Indonesia. Two of the six strategies overlapped between all main construction project stakeholders (i.e., consultants, contractors, and clients): (1) develop programs to integrate BIM into education curricula and academia, and (2) develop BIM implementation guidelines. These two strategies were highly correlated, and all project stakeholders had consistent views on their criticality for enhancing BIM implementation in Indonesia. The findings benefit policymakers by highlighting specific strategies that should take place to enhance BIM implementation in Indonesia.